Організаційні важелі впливу на процес ліцензування (допуску на ринок) у будівництві - Дмитренко, В. І. (Ways to Improve Construction Efficiency, 2014)
The general guidelines for the authorization of construction activity worldwide. The basic organizational methods of state regulation of the licensing process. A general list of organizational leverage on the licensing process of construction activities. Analyzed feasibility of construction activity around the world on the basis of ranking Doing Business.